Spillovers from foreign firms through worker mobility: an empirical investigation - Holger Görg; Eric Strobl (Leverhulme Centre for Research on Globalisation and Economic Policy, University of Nottingham, 2002)
While there has been a large empirical literature on productivity spillovers from foreign to domestic firms this literature treats the channels through which these spillover effects work as a black box. This paper attempts to fill this gap in the literature. Our results suggest that firms which are run by owners that worked for multinationals in the same industry immediately prior to opening up their own firm have higher productivity growth than other domestic firms. This suggests that these entrepreneurs bring with them some of the knowledge accumulated in the multinational which can be usefully employed in the domestic firm. We do not find any positive effects on firm level productivity if the owner had experience in multinationals in other industries, or received training by multinationals.
Keywords: 330; Arbeitsmobilität; Multinationales Unternehmen; Spillover-Effekt; Unternehmensentwicklung; Verarbeitendes Gewerbe; Ghana